1997
DOI: 10.1242/dev.124.12.2387
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced cardiogenesis in embryonic stem cells overexpressing the GATA-4 transcription factor

Abstract: GATA-4 is a cardiac-specific member of the GATA family of zinc finger transcription factors. During embryogenesis, GATA-4 expression is detected very early in the cardiogenic area and persists later in the developing heart. Studies have shown that GATA-4 is a potent transcriptional activator of several cardiac muscle-specific genes and a key regulator of the cardiomyocyte gene program. Consistent with a role for GATA-4 in cardiomyocyte formation, inhibition of GATA-4 expression by antisense transcripts interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 261 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…The primary screening using a reporter gene assay and the in vitro cell culture studies revealed several biologically active compounds, i.e., 3, 4, 5, 6, and 7, with distinct profiles. The structure−activity relationship studies of inhibitory compounds 3, 4, and 5 demonstrated the indispensable role of the two heavy atom linker together with a hydrogen acceptor feature next to the five-member ring, while a completely opposite agonistic effect was achieved by introducing a substituted fivemember ring into the amide bond (7). In the cardiomyocyte cultures, the compounds either augmented or inhibited the hypertrophic agonist-induced ANP and BNP expression.…”
Section: ■ Discussion and Conclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…The primary screening using a reporter gene assay and the in vitro cell culture studies revealed several biologically active compounds, i.e., 3, 4, 5, 6, and 7, with distinct profiles. The structure−activity relationship studies of inhibitory compounds 3, 4, and 5 demonstrated the indispensable role of the two heavy atom linker together with a hydrogen acceptor feature next to the five-member ring, while a completely opposite agonistic effect was achieved by introducing a substituted fivemember ring into the amide bond (7). In the cardiomyocyte cultures, the compounds either augmented or inhibited the hypertrophic agonist-induced ANP and BNP expression.…”
Section: ■ Discussion and Conclusionmentioning
confidence: 99%
“…The precipitated product was filtered, washed with n-heptane (2 × 50 mL), and dried under vacuum at 45 °C overnight to yield 8.52 g (62%) of compound 3 as an offwhite powder. NMR: 10.12 ppm (s, 1H, NH), 7 4-[(4-Propoxybenzylidene)amino]-5-(pyridin-4-yl)-4H-1,2,4triazole-3-thiol (4). A mixture of 4-propoxybenzaldehyde (10.00 g, 60.9 mmol) and 4-amino-5-(pyridin-4-yl)-4H-1,2,4-triazole-3-thiol (11.8 g, 60.9 mmol) in glacial acetic acid (100 mL) was heated to reflux for 2.5 h, and the solution was filtered hot.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…To study the underlying mechanism of cardiac developmental toxicity induced by CsA, expression levels of genes correlated with cardiac development, and apoptosis were detected by qPCR. GATA4 is one of the earliest developing transcription factors during heart development, and its up-regulated expression can promote the differentiation of embryonic stem cells into heart ( Grepin et al, 1997 ). Nkx2.5 regulates cardiac tube elongation and has different effects on the number of ventricular and atrial cells ( Targoff et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%